The Effect of Variations in Calcination Temperature on the Character of ZnO and ZnO/Mopl-CTAB in Degrading Methyl Orange - Aulia Dewi Rosanti; Fahmi Hidayat; Yuly Kusumawati; Arif Fadlan; Rizky Arief Shobirin; Fanni Kurnia Wijaya (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Medan orange peel (Mopl), which has been modified using cetyltrimethylammonium bromide (CTAB), has the potential to adsorb methyl orange (MO), and thus it can be used as a supporting material for ZnO. The ZnO is a photocatalytic material that is environmentally friendly, inexpensive, non-toxic, and has a wide band gap value. This study aims to determine the effect of calcination temperature on ZnO and ZnO characteristics due to modification using Mopl-CTAB and its effect on the degradation of MO. This research was carried out by synthesizing ZnO and ZnO/Mopl-CTAB materials using impregnation method and varying the calcination temperatures at 150, 250, 350, and 450 °C. The solid material powder obtained was characterized by using Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX), Brunauer–Emmett–Teller (BET), Fourier Transform Infra Red (FTIR), X-ray Diffraction (XRD), and Diffuse Reflectance Spectroscopy (DRS). Based on the results of the characterization, greater calcination temperature can affect the characteristics of the photocatalyst, including its morphology, functional groups, crystal structure, crystal lattice, crystallinity, surface area, pore size, pore volume, and energy band gap. The MO photodegradation activity test using the synthesized material was conducted under dark and light conditions. The results of the test revealed that the best or optimum material to be used in degrading MO is a calcined material at 450 °C under light conditions. ZnO material using Mopl-CTAB is better in degrading ZnO/Mopl-CTAB 450 °C than ZnO 450 °C. This study found that ZnO material using Mopl-CTAB  had a percent removal of 78% in 50 min, while ZnO 450 °C only had a percent removal of 53% in 40 min. The reaction kinetics in dark and light conditions follow the pseudo-second-order kinetic model. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).